“MENJARAH” PULAU GAMBUT: KONFLIK DAN KETEGANGAN DI PULAU PADANG - M. Nazir Salim (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2013)
The article was saimed at describing the conflicts between the community, peasants at Pulau Padang, Meranti Islands Regency, and PT Riau Andalan Pulp and Paper (RAPP). The conflict started from the policy of The Minister of Forestry which allowed concession of HTI to RAPP at Pulau Padang. The problem was the permission itself as it took not only the area of farming lands but also the areas of settlement. The other problem was the environment itself. This was a result of RAPP. Various researches showed that Pulau Padang had thick peat. However, the permission for RAPP was to build industries and canals needing a lot of water. This would damage the environment whereas the peat ought to be protected. If tis is done, the serious damage of ecosystem at Pulau Padang will take place.